Photographs of the Face for Publication and Presentations - Marcos A. Vargas, DDS, MS (Journal of Prosthodontics, 2003)
PHOTOGRAPHS of a patient’s face provide an enormous amount of information for to guide diagnosis and treatment planning, as well as to document preoperative and postoperative conditions.